Gut microbiota in surgical and critically ill patients. Issue 3 (May 2020) - Ho, Kwok M; Kalgudi, Shankar; Corbett, Jade-Marie; Litton, Edward
Microbiota—defined as a collection of microbial organisms colonising different parts of the human body—is now recognised as a pivotal element of human health, and explains a large part of the variance in the phenotypic expression of many diseases. A reduction in microbiota diversity, and replacement of normal microbes with non-commensal, pathogenic or more virulent microbes in the gastrointestinal tract—also known as gut dysbiosis—is now considered to play a causal role in the pathogenesis of many acute and chronic diseases. Results from animal and human studies suggest that dysbiosis is linked to cardiovascular and metabolic disease through changes to microbiota-derived metabolites, including trimethylamine-N-oxide and short-chain fatty acids. Dysbiosis can occur within hours of surgery or the onset of critical illness, even without the administration of antibiotics. These pathological changes in microbiota may contribute to important clinical outcomes, including surgical infection, bowel anastomotic leaks, acute kidney injury, respiratory failure and brain injury. As a strategy to reduce dysbiosis, the use of probiotics (live bacterial cultures that confer health benefits) or synbiotics (probiotic in combination with food that encourages the growth of gut commensal bacteria) in surgical and critically ill patients has been increasingly reported to confer important clinical benefits, including a reduction in ventilator-associated pneumonia, bacteraemia and length of hospital stay, in small randomised controlled trials. However, the best strategy to modulate dysbiosis or counteract its potential harms remains uncertain and requires investigation by a well-designed, adequately powered, randomised controlled trial.